(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To identify and analyze digital technologies developed to guide care for people with intestinal ostomies. Method: Technological prospecting conducted through documentary research conducted between March and September 2024. Data collection took place in patent registration databases, theses/dissertation repositories, and mobile app stores, including educational technologies in Portuguese, English, and Spanish, with no time or geographic limitations. Results: The results were organized into the following categories: software/hardware, mobile app, virtual environment, and educational video. Twelve productions were included: one patent, five theses/dissertations, and six mobile apps. The patent refers to software/hardware for postoperative care; the theses/dissertations resulted in an app prototype, an app, a virtual environment, and two educational videos. Conclusion: The conclusion is that, although still incipient, the digital technologies analyzed in this research, with an emphasis on mobile applications, which predominate over other technologies, have the potential to strengthen health education, self-care, and nursing practice. Furthermore, they represent innovative strategies for providing guidance on intestinal ostomy care.